Interleukin 6 concentration elevation as a risk of carotid intimamedia thickness in chronic kidney disease patients with dialysis - Riri Andri Muzasti; Herman Hariman; Elvita Rahmi Daulay (Medicinski glasnik, 2020)
Aim: To investigate the relationship between IL-6 concentration and the risk of carotid artery calcification in chronic kidney disease patients with dialysis (CKD-5D). Methods: This analytic observational cross-sectional study includes 95 clinically stable patients who underwent regular haemodialysis for at least three months at Rasyida Renal Hospital Medan, Indonesia. Serum IL-6 level was measured using the enzyme-linked immunosorbent assay (ELISA). Carotid artery calcification was determined by measuring Carotid Intima-Media Thickness (CIMT) using Real-Time B-mode ultrasound. Results: There were 53 males (55.8%) of the total samples with the mean duration of haemodialysis of 81.28±67.40 months. Ultrasound examination showed that 28 samples (29.5%) had carotid artery calcification. Statistical test significantly showed that patients with IL-6 ?81.1 pg/mL were more likely to have carotid artery calcification with an increased risk of 12.92 times (95% CI: 5.54-30.12) compared to the group of patients who had IL-6 level <81.1 pg/mL (p <0.001). Conclusion: This study proves that a high level of IL-6 can increase the risk of carotid artery calcification in CKD-5D patients.
Keywords: chronic kidney disease; interleukin-6; carotid intimamedia thickness